(untitled) (International Journal of Environmental Sciences, 2025)
Background: Thyroid nodules are a common clinical finding, and distinguishing benign from malignant lesions is crucial for determining the need for surgical intervention. Ultrasonography (USG) and fine needle aspiration cytology (FNAC) are primary tools in preoperative evaluation, while histopathology remains the gold standard. Objective: To correlate ultrasonographic findings with FNAC results in the diagnosis of malignancy in thyroid lesions, using histopathological examination (HPE) as the definitive reference. Material and Methods: This prospective study included 120 patients with thyroid swellings who underwent high-resolution ultrasonography and FNAC, followed by surgical excision and histopathological evaluation when indicated. Sonographic features suggestive of malignancy were recorded and FNAC findings were categorized according to the Bethesda System. Statistical correlation between USG, FNAC, and HPE was analyzed using standard diagnostic indices. Results: Colloid goitre and multinodular goitre were the most frequent diagnoses on both USG and FNAC. USG identified 5 nodules as suspicious for malignancy, while FNAC confirmed malignancy in 4 cases. Histopathology corroborated the FNAC findings. The combined use of USG and FNAC improved diagnostic accuracy, particularly in benign and malignant lesions, though FNAC demonstrated higher specificity when used alone. Conclusion: FNAC remains a reliable and specific diagnostic tool in the evaluation of thyroid nodules. Its accuracy is further enhanced when combined with ultrasonography. Correlating both modalities with histopathology ensures more precise patient selection for surgical management and reduces unnecessary thyroidectomies.